Profitability of precision phosphorus application on a commercial farm in the Heidelberg district, Western Cape - Hough, Ella Christina (University of the Free State, 2010)
Phosphorus (P) is an important nutrient required by every living plant and animal cell, and deficiencies in soils could cause a restriction on crop production. P is also a primary nutrient essential for root development and crop production, and are needed in the tissues of a plant where cells rapidly divide and enlarge. Precision agriculture (PA) could assist the farmer in applying the prescribed amount of P to the part of the field where it is required. Variable rate technology (VRT) is therefore a tool that can help with the development of strategies for phosphate fertiliser management. The main objective of this research is to determine the effect of precision P application on the profitability of PA on a commercial farm in the Heidelberg district in the Western Cape Province in South Africa. The study was conducted in collaboration with Mr Gildenhuys (on-farm trials) in the Heidelberg district in the Western Cape, South Africa. Four fields, totalling 106 ha, were identified as research fields for the study. The main crops included in the study were wheat, canola and barley (third year). As many as five soil types were found in each field, which was divided into two halves. One half was planted by making use of VRT, and the other half was planted by conforming to the traditional farm management system or single rate (SR). The same crop was planted on both halves. Wheat, canola and barley were used in a crop rotation system. The specific objectives were to determine the winter grain response to P on different soil types, the relationship with and effect of previous and current years’ yields on the following year’s P application and whether spatial econometric models are more accurate than traditional ordinary least squares (OLS) models in predicting the profitability impact of P on PA. The results obtained show significant differences between OLS, spatial error (SER) and restricted maximum-likelihood (REML) models. All the measures of goodness of fit indicated an increase in fit from the OLS to the SER model, with the best fit being achieved with the REML model, implying that the use of this model resulted in more accurate estimates. Profit analysis based on the application of statistical models indicates that, on average, the VRT treatment resulted in higher profits than the SR treatment. It could not be established, based on this study, that yield response to fertiliser depends on a specific soil type, because some soil types delivered higher yields and profits during certain years and during others they performed considerably weaker. It can thus be concluded that yield responses and profits differ from year to year and also within the crop rotation system (wheat, canola and barley). From the conclusions generated in hypothesis testing it is evident that the wheat crop yield response to P varied according to soil type. Over a three-year period, the VRT application of P lead to higher profitability compared to the SR application of P.

Fosfate (P) is ‘n belangrike voedingstof wat deur elke lewende plant- en diersel benodig word en tekorte aan hierdie voedingstof in grond kan lei tot ŉ beperking van oeste. Fosfate is ook die hoofvoedingstof wat benodig word vir wortelontwikkeling en voedselproduksie. Dit word benodig in die weefsel van plante waar selle vinnig verdeel en groei. Presisie-boerdery (PB) kan die boer help om die korrekte hoeveelheid P toe te dien in die gedeelte van die veld waar dit die meeste vereis word. Veranderlike-toedieningspeiltegnologie (VTT) is ŉ potensiële hulpmiddel vir die ontwikkeling van strategieë vir fosfaatbemestingbestuur. Die hoofdoel van hierdie navorsing is om die uitwerking van presisiefosfaataanwending op die winsgewendheid van PB op ‘n kommersiële plaas in die Heidelbergdistrik in the Wes-Kaap Provinsie in Suid-Afrika te bepaal. Die studie is in samewerking met mnr. Gildenhuys (proefneming op plase) in the Heidelbergdistrik in the Wes-Kaap in Suid-Afrika uitgevoer. Vier landerye wat gesamentlik 106 ha beslaan, is geïdentifiseer as navorsingsveld vir die studie. Die belangrikste gewasse wat by die studie ingesluit is, was koring, kanola en gars (derde jaar). In elke landery is soveel as vyf grondsoorte aangetref. Elke landery is in twee helftes verdeel. Die een helfte is beplant deur gebruik te maak van VTT, en die ander helfte is beplant deur gebruik te maak van die tradisionele plaasbestuurstelsel (ETT enkelpeiltoedieningstegnologie). Dieselfde gewas is op die twee helftes van die landerye geplant. Koring, kanola en gars is aangewend volgens ŉ oesrotasiestelsel. Die spesifieke doelwitte van die navorsing was om die reaksie van wintergraan te bepaal met die toediening van P op verskillende grondsoorte, sowel as die verband tussen die huidige en vorige jare se oeste op die volgende jaar se toediening van P, en om te bepaal of ruimtelike ekonometriese modelle meer akkurate resultate lewer as die gewone kleinste kwadraatmodelle (GKK-modelle) in die voorspelling van die winsgewendheidsimpak van P op PL. Betekenisvolle verskille is waargeneem tussen die resultate gelewer met GKK-, ruimtelike fout-modelle (RF) en beperkte maksimum voorkoms-modelle (BMV-modelle). Met die toepassing van maatreëls om die geskiktheid van die verskillende modelle, vanaf die GKK- tot die RF-modelle te bepaal, is bevind dat die akkuraatste skattings met die BMV-model verkry is en dit impliseer dat meer akkurate skattings met hierdie model gemaak kan word. ŉ Winsontleding is toegepas, gebaseer op die gebruik van statistiese modelle, wat aangedui het dat die veranderlike toedieningspeil- (VT-) behandeling groter winste gelewer het as die enkelpeiltoediening- (ET-) behandeling. Die navorsing kon nie bewys dat die grootte van oeste afhang van ‘n spesifieke grondsoort in die landerye nie, omdat sekere grondsoorte groter oeste en beter produksie gelewer het gedurende sekere jare en gedurende ander jare swakker oeste opgelewer het. Daar kan dus afgelei word dat oeste en winste van jaar tot jaar en binne die oesrotasiestelsel (koring, kanola en gort) sal verskil. Met die hipotese-toetsing is tot die gevolgtrekking gekom dat die koringoesreaksie op P volgens grondsoort verskillende resultate opgelewer het. Oor ŉ driejaar-periode het die VT-aanwending van P tot beter winsgewendheid gelei in vergelyking met die ET-aanwending van P. Ruimtelike ekonometriese modelle het ook gelei tot meer akkurate skattings as wat met die GKK-modelle bereik is.
Thesis (Ph.D. (Agricultural Economics))--University of the Free State, 2010
Keywords: Precision agriculture; Variable-rate application; Single rate application; Profitability; Spatial lag and error models; Restricted maximum-likelihood model; Phosphate; South Africa; Precision farming -- South Africa -- Heidelberg; Winter grain -- Fertilizers; Phosphatic fertilizers; Agriculture -- Research -- On-farm; Agriculture -- Economic aspects -- South Africa -- Heidelberg; Precision farming -- Economic aspects -- South Africa -- Heidelberg